PENGARUH PERASAN BUAH MENGKUDU TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS TANJUNG SARI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN TAHUN 2024 - Syntia Agustina; Herlina; Nova Nurwinda Sari (Universitas Muhammadiyah Klaten, 2025)
Treatment of high blood pressure or hypertension can be done by pharmacological and non-pharmacological methods. Non-pharmacological treatment involves consuming herbal plants which are believed to be able to reduce high blood pressure, one of which is noni fruit juice. The aim of this research is to determine the effect of noni fruit decoction on reducing blood pressure in hypertension sufferers in the Tanjung Sari Community Health Center Working Area, Natar District, South Lampung Regency in 2024. This type of research is quantitative, quasi-experimental design, one group pre test and post test design approach. The sample in this study were hypertension sufferers in the Tanjung Sari Community Health Center Working Area, Natar District, South Lampung Regency, totaling 32 respondents. The sampling technique in this research used purposive sampling. The test used uses a paired t-test. Based on statistical tests, a p-value of 0.000 or p-value < 0.05 was obtained, which means that there is an effect of giving noni fruit juice on reducing blood pressure in hypertension sufferers in the Tanjung Sari Community Health Center Working Area, Natar District, South Lampung Regency in 2024. The average systolic blood pressure before and after being given noni fruit juice was from 164.38 mmHg to 130.94 mmHg. Meanwhile, the average diastolic blood pressure was from 110 mmHg to 84.69 mmHg. This means that it is proven that giving noni fruit juice has the effect of reducing hypertension or blood pressure.